2017
DOI: 10.1002/adfm.201604688
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Assisted Synthesis of IrCu Hollow Octahedral Nanocages as Highly Active Electrocatalysts toward Oxygen Evolution Reaction

Abstract: Development of oxygen evolution reaction (OER) catalysts with reduced precious metal content while enhancing catalytic performance has been of pivotal importance in cost‐effective design of acid polymer electrolyte membrane water electrolyzers. Hollow multimetallic nanostructures with well‐defined facets are ideally suited for saving the usage of expensive precious metals as well as boosting catalytic performances; however, Ir‐based hollow nanocatalysts have rarely been reported. Here, a very simple synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
141
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(148 citation statements)
references
References 60 publications
7
141
0
Order By: Relevance
“…Ru‐ and Ir‐based catalysts have demonstrated promising electrocatalytic activity for the OER, yet these precious metal catalysts are expensive and scarce. As a means of reducing the usage of precious metals, Ru‐ or Ir‐based nanocage and nanoframe structures have been investigated for the OER . They have shown enhanced OER activities as a result of their enlarged catalytically active surface areas per unit mass.…”
Section: Introductionmentioning
confidence: 99%
“…Ru‐ and Ir‐based catalysts have demonstrated promising electrocatalytic activity for the OER, yet these precious metal catalysts are expensive and scarce. As a means of reducing the usage of precious metals, Ru‐ or Ir‐based nanocage and nanoframe structures have been investigated for the OER . They have shown enhanced OER activities as a result of their enlarged catalytically active surface areas per unit mass.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] This effect has been rationalized by d-band center theory, a descriptor for the relationship between the distribution of d-band electron and adsorption energy. [32][33][34] By exposing the high-density external and internal surfaces to reactants, collision frequency between reaction sites and active species can be increased, leading to the enhanced catalytic performance. Nanocrystals of hollow feature such as nanoframes and nanocages can reduce the amount of expensive precious metals and expose more active surface area.…”
mentioning
confidence: 99%
“…[34,[36][37][38][39] Compared with the bulk solid counterparts,h ollow configurations with larger surface areas usually endow catalysts with ah igher density of surface-exposed active sites.Moreover,their large void space could effectively reduce ionic transport resistance and the ion diffusion lengths for surface reactions. [34] Very recently,afew pioneering studies have described the successful generation of hollow nanostructured (oxy)hydroxides towards water oxidation with encouraging results.…”
mentioning
confidence: 99%
“…[34] Very recently,afew pioneering studies have described the successful generation of hollow nanostructured (oxy)hydroxides towards water oxidation with encouraging results. [37,38,[40][41][42][43][44][45][46] Forexample,Y an and co-workers have reported the synthesis of a-Ni(OH) 2 hollow nanospheres through at emplate-free method. [40] Thea s-obtained hierarchical hollow nanospheres displayed enhanced OER activity compared with b-Ni(OH) 2 nanoplates/nanoparticles.S hi et al have reported the preparation of VOOH hollow nanospheres through as imilar hydrothermal strategy.…”
mentioning
confidence: 99%